The Phenolic Quality of Red Grapes at Delivery: Objective Evaluation with Colour Measurements - Celotti, E.; Carcereri De Prati, G. (South African Journal of Enology and Viticulture, 2017)
The current research evaluated the possibility of the real time (before crushing) measurement of the phenolic quality index of red grapes to define the true quality of the raw material destined for the production of wine or juice. The measurement procedure involved the use of a spectrometer and the acquisition of a reflectance spectral signal via optical fibres immersed directly in the sample to be analysed. The measurements were done on the same juice (grape must) used for refractometry analysis of the sugars. It was established that it was possible to objectively classify the red grape cultivars tested on the basis of their anthocyanin and total polyphenol content. The experiments done in the winery and laboratory demonstrate a positive correlation between the colour of the must sampled from the grape at delivery and the total polyphenols in that grape. The colorimetric parameter can be acquired instantly and the data used in real time to improve the management of the winemaking process and to pay for the grapes on the basis of their phenolic quality.